IDENTIFICATION OF CONSUMER PERSPECTIVES ON DISCOUNT OFFERS AT DAKNALGAE RESTAURANT GADING SERPONG - Harthur Karnadi; Khenia Kartika Sari; Leonardo Stanley Hubert; Levina Nathania Budhiman; Livia Margarita; Mahatma Kevin Tio (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to identify consumer perspectives on discount offers and their influence on consumer behavior at Daknalgae Restaurant Gading Serpong. Using a qualitative approach, the research employs in-depth interviews with customers and the restaurant owner to gain insights into how discounts are perceived in relation to consumer behavior, perception, and loyalty. The findings reveal that discount offers can increase consumer interest in trying products, expand market reach, and encourage repeat visits. However, long-term dependence on discount strategies may lower consumers’ perception of product quality and create loyalty that is solely price-driven. Therefore, discount strategies should be balanced with improvements in product quality and service to foster sustainable consumer loyalty.